UPAYA MENINGKATKAN MINAT DAN HASIL BELAJAR GEOGRAFI KONSEP PEDOSFER MELALUI STRATEGI PEMBELAJARAN KOOPERATIF TIPE INVESTIGASI KELOMPOK PADA SISWA KELAS X IPS 2 SMA NEGERI I MAUMERE - GENSIANA LODAN (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
The objectives of this CAR are: (a) To increase the interest in learning geography in the Pedosphere concept, (b) To increase the learning outcomes of Geography in the Pedosphere concept through cooperative learning models of Group investigation in Class X IPS 2 of SMA N 1 Maumere in 2018/2019. PTK is done through 2 cycles. Data collected in this study consisted of quantitative data and qualitative data. Quantitative data obtained from test results were processed using percentage descriptions. The scores obtained by students were averaged to find the level of understanding of the pedosphere concept of students in learning Geography. Qualitative data obtained from students' observations and questionnaires were classified based on aspects that were the focus of the analysis. These quantitative and qualitative data are then linked as a basis for describing the successful implementation of the group investigation learning model which is characterized by an increase in student interest and learning outcomes in the learning of pedospheric geography in classical geographical learning. The results showed that the cooperative learning model of group investigation type applied to the learning of the pedosphere concept geography proved to be able to increase student learning interest both individually and classically, foster the ability to cooperate, think critically, and at the same time also increase student learning outcomes significantly that is, from the average score of 59 students in pre-cycle, to 67.5 in cycle 1 and increased to 79 in cycle 2. So that the learning of the pedosphere concept Geography with the cooperative learning model of group investigation is proven to be able to improve the cognitive, affective and psychomotor aspects of students .